Pirate Tales. - Deary, Terry (Pirate Tales Ser., 2011)
Grace O'Malley is the greatest pirate that ever lived, the terror ofthe Irish Sea. Her gang of cut-throats rule the waves ... until Grace iscaptured! But instead of being hanged, she is sent to London - by royalcommand. What will happen when the Queen of the Pirates meets the Queenof England?